Menguji Anteseden-Anteseden dari Online Impulse Buying Behaviour pada e-Commerce - Intan Muliana Rhamdhani (Pusat Riset dan Inovasi Nasional, 2025)
The switching of consumer purchases from offline to online is an interesting phenomenon to conduct in-depth investigation. This triggers consumers to make impulsive purchases online. Thus, the purpose of this study is to investigate the antecedents that have the potential to increase online impulse buying behavior, namely, hedonic shopping motivation, urge to buy, and positive emotion. This study used 100 respondents who had made online impulse buying in e-commerce in Kebumen. Respondents were taken using purposive sampling technique, data was processed with the help of SPSS statistical software and analyzed using multiple regression analysis. The results of the study found that all hypotheses were accepted. Hedonoc shopping motivation, urge to buy, and positive emotion partially and simultaneously proved to have a positive effect on online impulse buying behavior. Another finding of this study is that urge to buy is the variable that has the greatest influence in increasing online impulse buying behaviour.